Correlation between Screen Time, Outdoor Activity, and Myopia Progression in Urban School-aged Children: A Concise Review - Singh, Shubhanshi; Tyagi, Trisha; Bano, Razia; kaur, Sandeep; Saumya, Saumya (Journal of Neonatal Surgery, 2025)
The prevalence of myopia in school-aged children has increased dramatically in recent decades, particularly in urban populations. This review examines current evidence on the relationships between digital screen exposure, outdoor activity, and myopia development in urban school-aged children and adolescents, focusing on research published between 2020-2025. Recent studies consistently demonstrate strong associations between increased screen time, reduced outdoor exposure, and myopia progression. The COVID-19 pandemic has exacerbated these relationships through increased digital learning and reduced outdoor activities. We evaluate methodological approaches to measuring screen time and outdoor activity, highlighting objective assessment tools. Intervention studies indicate that structured increases in outdoor time and regulated screen use can effectively slow myopia progression. We conclude with recommendations for evidence-based guidelines and future research directions to address this growing public health concern in urban environments.